2012
DOI: 10.1515/roe-2012-0205
|View full text |Cite
|
Sign up to set email alerts
|

Was sind die richtigen Rentenabschläge? – neue Perspektiven

Abstract: SummaryThe correct adjustment of pension benefits when postponing retirement is calculated by three „income-oriented“ approaches: the incentive-neutral approach, the budget-neutral approach and as an innovation the return-neutral approach. It turns out, that the three approaches differ just in their underlying discount rate but not in their method of calculation. In addition it can be shown, that the incentive-neutral approach leads to incentive neutrality when the implicit taxation of contributions is equal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…4 The determination of the discount rate δ is a crucial issue. In fact, it will turn out that different approaches to calculate appropriate deductions differ primarily in their choice of the discount rate (see also Gasche 2012). If the costs of early retirement have to be financed by debt then the market interest rate seems to be the right choice, i.e.…”
Section: Deductions For a General Discount Ratementioning
confidence: 99%
See 3 more Smart Citations
“…4 The determination of the discount rate δ is a crucial issue. In fact, it will turn out that different approaches to calculate appropriate deductions differ primarily in their choice of the discount rate (see also Gasche 2012). If the costs of early retirement have to be financed by debt then the market interest rate seems to be the right choice, i.e.…”
Section: Deductions For a General Discount Ratementioning
confidence: 99%
“…(2003)]. Overviews of the debate can be found in Börsch-Supan (2004) and Gasche (2012). The latter, e.g., has shown that the main difference between the two concepts of incentive neutral and budget neutral adjustment rates is the choice of the underlying discount rate, where a risk-free rate is the appropriate choice for the first and the IRR for the second concept.…”
Section: Related Literature and Main Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…If an individual's choice of claiming age should be neutral to the sustainability of the pension system, these adjustment factors must be actuarially neutral, i.e., they should equalize the present discounted value of pension benefits across all permissible claiming ages. Depending on age and life expectancy, actuarial adjustment rates are between 6.5 and 8 percent (Börsch-Supan, 2004;Queisser & Whitehouse, 2006;Werding, 2007 andGasche, 2012;OECD, 2015). In most European countries, however, they are substantially lower (Table 1).…”
Section: New Zealandmentioning
confidence: 99%